IMPRESI ORANG RIMBA: â€œMELANGUNâ€ SEBUAH KOMPOSISI MUSIK DALAM INTERPRETASI PERJALANAN ORANG RIMBA - Sidik, Hadaci (Puitika, 2016)
Orang Rimba is classical, one-part composition for orchestra, inspired by Orang Rimbaâ€™s tradition and characteristic style of life. Melangun is an obligation to move from one place to another in a case of serious threat or death one of the tribe members. Development of knowledge, technology and constantly growing human needs affect the Orang Rimbaâ€™s life cycle. Illegal logging, huntings, factory building, development of human settelemnents, palm and rubber plantations slowly destroy natural Kubuâ€™s environment. Â Keywords: orang rimba, Melangun, komposisi musik